Pendampingan Perilaku Hidup Bersih dan Sehat Berbasis Gereja di Sekolah Minggu Jemaat Gereja Protestan Maluku (GPM) Tihulale Kabupaten Seram Bagian Barat - Resa Dandirwalu; Desviana Maspaitella; Nining Gan; Yonaria Pattiapon; Vonda Leasa; Pingkan P. Alfons; Jems Porumau; Eveline L. Kastanja; Dennyela P. Siwabessy; Koce Tuatanasy; Melina Letelay; Rezky B. Tahalea; Yusuf R. Serpiela; Marsel Mangar (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Clean and healthy lifestyle is essential for all people especially children. Based on preliminary study, Sunday School Children of the GPM Tihulale Church had less adequate knowledge and skills regarding the habits of clean and healthy lifestyle. Therefore, this community service was carried out to improve clean and healthy attitudes as well as behaviors of Sunday School Children of the GPM Tihulale Church. The program was conducted through counselling and training and covered five stages: interviewing and analyzing the partners’ needs, educating about clean and healthy behavior, giving health education and training on clean and healthy behavior, distributing free toothbrushes and toothpastes, and conducting evaluation and follow-up activities. The results obtained were an increase in children’s knowledge and skills about clean and healthy lifestyle during their time in the Sunday School Service and daily lives.